2017
DOI: 10.1016/j.nicl.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter alterations in migraine: A systematic review and meta-analysis

Abstract: ObjectivesTo summarize and meta-analyze studies on changes in grey matter (GM) in patients with migraine. We aimed to determine whether there are concordant structural changes in the foci, whether structural changes are concordant with functional changes, and provide further understanding of the anatomy and biology of migraine.MethodsWe searched PubMed and Embase for relevant articles published between January 1985 and November 2015, and examined the references within relevant primary articles. Following exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
139
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(154 citation statements)
references
References 82 publications
13
139
2
Order By: Relevance
“…A previous study involving both episodic and chronic migraineurs has similarly demonstrated that the temporal lobe is involved in increased cortical thickness covariance compared to controls . Similarly, the frontal lobe has previously been identified as one of the regions with cortical changes in migraine . Our results further corroborate the importance of the temporal and frontal lobes in CM pathophysiology.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study involving both episodic and chronic migraineurs has similarly demonstrated that the temporal lobe is involved in increased cortical thickness covariance compared to controls . Similarly, the frontal lobe has previously been identified as one of the regions with cortical changes in migraine . Our results further corroborate the importance of the temporal and frontal lobes in CM pathophysiology.…”
Section: Discussionsupporting
confidence: 88%
“…The postcentral gyrus, paracentral lobule, and precentral gyrus are involved in sensorimotor networks, and a previous study found functional abnormalities and abnormal cortical thickness or gray matter volume in the sensorimotor network in migraineurs [9,41,42]. Gray matter volume decreases in the right anterior cingulate are related to the estimated frequency of headache attacks [43]. The temporal pole has been demonstrated to participate in pain processing and multisensory integration [3,35,36].…”
Section: Discussionmentioning
confidence: 97%
“…In particular, VBM data established that the GMV was decreased in the anterior cingulate cortex, insula, amygdala, parietal operculum, middle and inferior frontal gyrus [13]. In addition, regions with reduced grey matter density are located in bilateral insula, motor premotor, prefrontal, cingulate cortex, right posterior parietal cortex and orbitofrontal cortex [14].…”
Section: Discussionmentioning
confidence: 98%